High body clearance and low oral bioavailability of alantolactone, isolated from Inula helenium, in rats: extensive hepatic metabolism and low stability in gastrointestinal fluids. (April 2016) - Lee, Jae‐Young; Kim, Sang‐Bum; Chun, Jaemoo; Song, Kwang Ho; Kim, Yeong Shik; Chung, Suk‐Jae; Cho, Hyun‐Jong; Yoon, In‐Soo; Kim, Dae‐Duk
Abstract: Alantolactone (ALA) is a major bioactive sesquiterpene lactone present in the roots of Inula helenium L. (Asteraceae) which has been used widely in traditional medicine against various diseases such as asthma, cancer and tuberculosis. The pharmacologic activities of alantolactone have been well characterized, yet information on the physicochemical and pharmacokinetic properties of alantolactone and their mechanistic elucidation are still limited. Thus, this study aims to investigate the oral absorption and disposition of alantolactone and their relevant mechanisms. Log P values of alantolactone ranged from 1.52 to 1.84, and alantolactone was unstable in biological samples such as plasma, urine, bile, rat liver microsomes (RLM) and simulated gastrointestinal fluids. The metabolic rate of alantolactone was markedly higher in rat liver homogenates than in the other tissue homogenates. A saturable and concentration‐dependent metabolic rate profile of alantolactone was observed in RLM, and rat cytochrome P450 (CYP) 1 A, 2C, 2D and 3 A subfamilies were significantly involved in its hepatic metabolism. Based on the well‐stirred model, the hepatic extraction ratio (HER) was estimated to be 0.890–0.933, classifying alantolactone as a drug with high HER. Moreover, high total body clearance (111 ± 41 ml/min/kg) and low oral bioavailability (0.323%) of alantolactone were observed in rats. Taken together, the present study demonstrates that the extensive hepatic metabolism, at least partially mediated by CYP, is primarily responsible for the high total body clearance of alantolactone, and that the low oral bioavailability of alantolactone could be attributed to its low stability in gastrointestinal fluids and a hepatic first‐pass effect in rats. Copyright © 2016 John Wiley & Sons, Ltd.